2004
DOI: 10.1074/jbc.m401317200
|View full text |Cite
|
Sign up to set email alerts
|

An Hsp27-related, Dominant-negative-acting Intracellular Estradiol-binding Protein

Abstract: New World primates (NWPs) exhibit a compensated form of resistance to gonadal steroid hormones. We demonstrated recently that estrogen resistance in NWP cells was associated with the overexpression of two proteins, a nonreceptor-related, dominant-negative-acting estrogen response element (ERE)-binding protein (ERE-BP) and an intracellular estradiol-binding protein (IEBP). Based on the N-terminal sequences of tryptic fragments of IEBP isolated from a 17␤-estradiol (E 2 ) affinity column we cloned a full-length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…This process can be modified by various intracellular proteins as they can either complex with the ER machinery to augment or inhibit ERE binding or interact directly with the ERE thus altering estrogenic signaling. HSP27 is capable of suppressing ERE-mediated transcription at the ERE by acting as an intracellular estradiol-binding protein in mammals [Chen et al, 2004[Chen et al, , 2008. The HSP70 family can be divided into 2 subfamilies, a cognate or constitutive type (HSC70) and an inducible form (HSP70).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process can be modified by various intracellular proteins as they can either complex with the ER machinery to augment or inhibit ERE binding or interact directly with the ERE thus altering estrogenic signaling. HSP27 is capable of suppressing ERE-mediated transcription at the ERE by acting as an intracellular estradiol-binding protein in mammals [Chen et al, 2004[Chen et al, , 2008. The HSP70 family can be divided into 2 subfamilies, a cognate or constitutive type (HSC70) and an inducible form (HSP70).…”
Section: Discussionmentioning
confidence: 99%
“…one-month-old gonadal tissue from alligators HSP27 mRNA was significantly elevated in testicular tissue when compared to ovarian tissue of the same age. HSP27 can function as a suppressor of estrogen response element (ERE)-mediated transcription by competing with the estrogen receptor (ER) [Chen et al, 2004[Chen et al, , 2008; i.e., estrogenic signaling requires that the ligand (under normal conditions an endogenous estrogen) binds the ER which then dimerizes and translocates to the DNA where it binds to an ERE in the promoter of an estrogen-inducible gene. This process can be modified by various intracellular proteins as they can either complex with the ER machinery to augment or inhibit ERE binding or interact directly with the ERE thus altering estrogenic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…GCUNC45, an Hsp90 cochaperone, effectively blocks the progression of progesterone receptor chaperoning in the presence of Hsp90beta [31]. Hsp27 was known to dysregulate the interaction of estrogen receptor with chromatin and acts as a suppressor of estrogen-induced transcription [32,33]. Hsp27 was also shown to be phosphorylated in an androgen-dependent manner and enhanced the AR stability, shuttling and transactivation, thereby promoted the survival of prostate cancer cells [34].…”
Section: Bag-1m Is Not Involved In the Degradation Of Grmentioning
confidence: 99%
“…Based on characterization of the IDBP and IEBP in NWP cells, it was assumed that hsc70 and hsp27 act as intracellular 'decoys' for the relatively high levels of 1,25(OH) 2 D and E 2 present in NWPs, thereby attenuating over-exuberant VDR or ERα signaling. This is certainly true of hsp27 which suppresses E 2 -ERα-mediated gene transcription when over-expressed in human cells [92]. By contrast, studies using various in vitro models showed that over-expression of hsc70-like IDBP cloned from NWP cells enhanced 1,25(OH) 2 D-VDR-mediated gene transcription [93].…”
Section: Intracellular Binding Proteins and The Cytoplasmic Traffickimentioning
confidence: 93%